2019
DOI: 10.9734/ajeba/2019/v11i430135
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of Knowledge Creation Capability and Organizational Forgetting on Absorptive Capacity and Innovation Performance among SMEs: A Symmetrical Approaches

Abstract: Organizations needs knowledge creation capability and organizational forgetting to enrich their innovative performance in ever-changing business setting.The purpose of this article is to explore the influence of knowledge creation capability, organizational forgetting and absorptive capacity on Firm’s innovative performance. We test the model using Partial least squares structural equation modeling (PLS-SEM) to analyze empirical data collected from 194SMEs listed in Sri Lanka inventors’ commission.The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“… Raisal et al (2019) explored the effects of knowledge creation capability , U/IF, and absorptive capacity on firms’ innovative performance. The data were collected from 194 small- and medium-sized enterprises (SMEs; CEOs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Raisal et al (2019) explored the effects of knowledge creation capability , U/IF, and absorptive capacity on firms’ innovative performance. The data were collected from 194 small- and medium-sized enterprises (SMEs; CEOs).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the relationship between U/IF (updating routines and knowledge) and relearning jointly facilitating strategic flexibility, Zhao and Wang (2020) used survey data from 194 firms and found that U/IF promotes (fully mediates) organizational relearning, thereby improving strategic flexibility. Raisal et al (2019) explored the effects of knowledge creation capability, U/IF, and absorptive capacity on firms' innovative performance. The data were collected from 194 small-and mediumsized enterprises (SMEs; CEOs).…”
Section: U/if and Its Link To Organizational Capabilitiesmentioning
confidence: 99%
“…Innovation of the organizations concerned with generating new and novel ideas that how to apply new knowledge to produce new products and services and modification and improvement in existing ones (Leal-Rodríguez et al, 2014). Leadership styles projecting firm's expectations and passion that enhance firm's revolution by escalating the chances for their employees (Al-Husseini et al, 2019;Weintraub & McKee, 2019;Zheng et al, 2016)and promote organizational success and values (Meyer & Peng, 2016;Raisal et al, 2019). Leader's actions display the leading power behind managerial innovation (Ferreras Mendez et al, 2018).…”
Section: Leadership Styles (Tfl and Tsl) And Firms' Innovation: The Case Of Mediation Of Absorptive Capacity (Pac And Rac)mentioning
confidence: 99%
“…Earlier studies evidenced that both dimensions of absorptive capacity (PAC and RAC) work as an intervening mechanism for enhancing innovative performance (Daspit et al, 2019;Raisal et al, 2019;Wu et al, 2019) with different predicting variables. On the other side, the study conducted by Ahmad et al ( 2019) evidenced that PAC does not hold any intervening mechanism, but RAC has an indirect influence on the relationship of intellectual capital and business performance.…”
Section: Leadership Styles (Tfl and Tsl) And Firms' Innovation: The Case Of Mediation Of Absorptive Capacity (Pac And Rac)mentioning
confidence: 99%